2001
DOI: 10.1046/j.1525-1594.2001.025005371.x
|View full text |Cite
|
Sign up to set email alerts
|

Change in Vasoconstrictive Function During Prolonged Nonpulsatile Left Heart Bypass

Abstract: We investigated changes in vasoconstrictive function accompanying prolonged nonpulsatile left heart bypass (NLHB). After 2-week pulsatile left heart bypass (PLHB) in 11 goats, NLHB was conducted for another 4 weeks (Group N) in 6 goats. In the other 5 goats, PLHB was continued for another 4 weeks (Group P). Systemic vascular resistance at rest (rSVR) was measured on the last days of the second and sixth postoperative week (W2 and W6, respectively). Subsequently, phenylephrine was injected, and the maximum valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 18 publications
(18 reference statements)
1
31
0
1
Order By: Relevance
“…In contrast, during support with a continuous-flow LVAD, native pulsatility is nearly abolished 27 . Interestingly, there is significant evidence that prolonged non-pulsatile blood flow with a continuous-flow LVAD also produces arterial remodeling 28-31 similar the changes described in this report with a pulsatile pump. These studies and our data demonstrate that altered pulsatility (increased or reduced) produces architectural and functional arterial changes.…”
Section: Discussionsupporting
confidence: 79%
“…In contrast, during support with a continuous-flow LVAD, native pulsatility is nearly abolished 27 . Interestingly, there is significant evidence that prolonged non-pulsatile blood flow with a continuous-flow LVAD also produces arterial remodeling 28-31 similar the changes described in this report with a pulsatile pump. These studies and our data demonstrate that altered pulsatility (increased or reduced) produces architectural and functional arterial changes.…”
Section: Discussionsupporting
confidence: 79%
“…7 In addition, compensation for decreased venous return is inadequate due to poor contractile reserve, 8 and lower extremity reflexes are blunted due to chronic volume overload and neurohormonal activation. 9 Continuous-flow left heart bypass is shown to be associated with a marked decrease in vasoconstrictive function in animal models 10 ; however, similar human data are lacking. Patients are also seen to have impaired chronotropic reserve and an abnormal heart rate recovery early after continuous-flow LVAD placement, indicating significant cardiac autonomic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Animal [87] and human [88, 89] studies have shown that prolonged continuous flow caused significant changes in the aortic wall, including medial degeneration, smooth muscle cell (SMC) disorientation and depletion, elastic fiber fragmentation and depletion, medial fibrosis and atherosclerotic changes [89]. Such changes may translate to decreased peripheral vascular reactivity [90, 91]. It has been suggested that continuous flow leads to stiff and unresponsive arteries [92].…”
Section: Renal Function In the Long Runmentioning
confidence: 99%